Hypercalcemia Following Adrenalectomy for Cushing Syndrome in a Patient with Post-Surgical Hypoparathyroidism - Pietro Locantore; Alessandro Oliva; Gianluca Cera; Rosa Maria Paragliola; Roberto Novizio; Caterina Policola; Andrea Corsello; Alfredo Pontecorvi (Diseases)
Background: Hypercalcemia is a frequently encountered laboratory finding in endocrinology, warranting accurate clinical and laboratory evaluation to identify its cause. While primary hyperparathyroidism and malignancies represent the most common causes, many other etiologies have been described, including some reports of hypercalcemia secondary to adrenal insufficiency. On the contrary, hypoparathyroidism is a relatively common cause of hypocalcemia, often arising as a complication of thyroid surgery. In real-world clinical practice, however, many challenges come into play, and a comprehensive approach may not be enough to establish a diagnosis. Case presentation: we describe a peculiar case of severe hypercalcemia occurring in a 47-year-old woman with a previous history of post-surgical permanent hypoparathyroidism treated with calcitriol (0.5 µg bid) and calcium carbonate (1 g qd), which persisted after withdrawal of these drugs. During her follow-up, an ACTH-independent Cushing syndrome was diagnosed, leading to a unilateral right adrenalectomy. In the two months following surgery, she was admitted to the emergency ward on three occasions because of severe, persistent, idiopathic hypercalcemia. On each occasion, parathyroid hormone levels were confirmed to be undetectable, with low vitamin D levels. Common and rare causes of hypercalcemia were excluded, and the persistence of severely elevated calcium levels led to the empirical use of intravenous clodronate, achieving remission of both hypercalcemia and, unexpectedly, hypoparathyroidism. After 8 months, due to borderline-reduced calcium, calcitriol at 0.5 µg qd was restarted. After 18 months of follow-up, the patient is well and normocalcemic, with low-dose calcitriol. Notably, the patient had no acute adrenal insufficiency, distinguishing this case from other post-adrenalectomy hypercalcemia reports. Conclusions: the history of hypoparathyroidism makes this case even more unusual, and it encourages careful follow-up of hypoparathyroid patients with Cushing syndrome. Ongoing observation, as well as new research on the physiopathology of cortisol and calcium metabolism, are needed to clarify the pathogenesis of this case.